“Factores de riesgo materno asociado a displasia cervical en mujeres del distrito de morales periodo enero 94- Diciembre 96 - Chuquizuta Paredes, Ines (1997)
The present study is real hoisted with records of Pap smears taken in the health centre of Morales during the years 1994, 1995, 1996 a study of 809 taken PAPS of which 12 presented Neoplasia Cet-vical doing an incidence of 14.B per thousand live teas and a frequency of 01 positive case for every 66 negative samples. The main associated factors were; older than 25 years, number of children under 20 years of age greater than 2, age of onset of sexual intercourse and number of sexual partners more than 2, history of abortion. It says the need to expand and decentralize Neck Cancer screening services, as well as conducting forward-looking research with follow-up to quantify the evolution or regression of cervical neoplasia.